EDUKASI DAN PELATIHAN DATA SCIENCE UNTUK ANALISIS DATA KESEHATAN DALAM MENDUKUNG MASYARAKAT SEHAT DI KOTA PADANG PANJANG - Januardi Nasir; Yasha Langitta Setiawan; Gustri Efendi; Lido Sabda Lesmana (ASOSIASI IDEBAHASA KEPRI, 2026)
The development of information technology has brought significant changes to various areas of life, including healthcare. One rapidly developing technology is data science, a discipline that utilizes data processing, statistics, and computational techniques to generate useful information to support decision-making. In healthcare, data science can be used to analyze health data, identify disease patterns, support disease prevention programs, and improve the quality of public health services. However, public understanding and skills in utilizing data science for health data analysis are still relatively limited. Therefore, a Community Service (PKM) activity themed